Feelings about Math and Science: Reciprocal Determinism and Catholic School Education - Ghee, Anna Cash; Khoury, Jane C. (Catholic Education: A Journal of Inquiry and Practice, 2008)
Applying Bandura’s reciprocal determinism model, differences in math and science experiences influenced by individual, gender, and school variables were investigated within 1,368 elementary students who attended 21 Catholic schools. Math and Science were evaluated positively and favored more than other academic subjects. However, advantages were found for boys by lowered math anxiety levels and favoring of math, and for large schools by lowered math anxiety levels and higher student ratings of science. No advantages were found for small schools. However, school poverty rate appeared to have a confounding effect on school size. Discussion is presented pertaining to the specific need to study Catholic school systems regarding student perceptions in light of distinguishing Catholic school factors.